Mencari Tuhan di Tengah Scroll tanpa Henti - Hironimus Bandur; Selesius Eki Canggu; Maria Silfetreli Moi; Methildis Melania Bahanul; Viralius Jadut; Valentino Delans Kristoforus; Hendrikus Siu (CV. ALIM'SPUBLISHING, 2026)
The phenomenon of infinite scrolling in digital media reflects a fundamental shift in how modern individuals experience spirituality in the digital era. The continuous flow of information creates new spaces for the search for meaning, including the human relationship with the Divine, while simultaneously introducing challenges in the form of constant distraction that disrupts deep reflection. This study aims to analyze how infinite scrolling contributes to a crisis of spiritual awareness and how digital technology functions as an ambivalent space between distraction and reflection. The research employs a descriptive qualitative method with a library research approach, using relevant academic literature and religious documents. The findings indicate that intensive digital engagement reduces opportunities for contemplation, weakens reflective capacity, and produces shallow and fragmented spiritual experiences. However, digital technology also provides broad access to spiritual resources that can be used constructively. This study concludes that the crisis of spiritual awareness in the digital era is influenced not only by individual factors but also by technological structures shaping human attention. Therefore, digital literacy that includes ethical and spiritual dimensions is essential to ensure technology supports the search for meaning.